A frequency trend analysis of major and critical audit finding groupings for clinical trials involving central nervous system studies - Louw, Elma (My University, 2011)
Quality Assurance (QA) Audits are an essential component and an integral part of clinical trials. As a quality improvement tool, forming part of Good Clinical Practice (GCP) an audit can demonstrate that real efforts are being made to improve and enhance the quality of professional care to all trial subjects participating in clinical trials. Specifically, clinical research performed on the central nervous system (CNS) involves distinctive areas of concern to adherence to good clinical practice in this therapeutic area. For example an informed consent process not conducted appropriately for subjects with e.g. Schizophrenia or Alzheimer’s disease; or inter-individual rating differences in instances when different investigators (psychiatrist) assess a trial subject. A need was identified to analyze the association between the CNS indication audited and the audit findings and to perform a trend analysis that highlight re-occuring audit findings. A total of 123 CNS audit reports were obtained from the Quality Assurance Departments of Quintiles in South Africa and Europe. The audit reports were grouped into the 15 CNS indications that were audited. Five hundred and six (506) audit findings were derived from the 123 CNS audits reports. The audit findings were categorized according to GCP subject matter, regulatory requirements or Standard Operating Procedures (SOPs). The severity of audit findings was classified as critical or major. The results of this investigation suggested a need for substantial improvement in three important areas. Firstly; adherence to the study requirements inclusive of relevant Standard Operating Procedures (SOPs). Secondly the development of better defined protocols and thirdly training of monitors. Study planners and Clinical Trial Management should take a proactive role to minimize the audit findings by ensuring monitors with experience in the research field should be involved in the study. Procedures should be implemented to educate site staff. Focus should be placed on the importance of detailed source documentation, adherence to investigational product dosage requirements, the conduct of the informed consent process, and adequate study documentation maintenance.
MSc (Med), Pharmaceutical Affairs, Faculty of Health Sciences, University of the Witwatersrand
Keywords: drug trials; findings; central nervous system; clinical trials; quality audit